2019
DOI: 10.1590/1413-81232018243.07112017
|View full text |Cite
|
Sign up to set email alerts
|

Efect of vitamin A suplementation: a systematic review

Abstract: To evaluate the effect of vitamin A supplementation in postpartum infants and women on serum retinol levels and breast milk. The databases Medline, PubMed, Lilacs and SciELO were consulted. The descriptors used were vitamin A, dietary supplement, child, postpartum period, infant and nutrition programs policies. Search found 7432 articles. After elimination of duplicity and application of eligibility criteria, 8 studies remained. All evaluated the effect of vitamin A supplementation on immediate postpartum, fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 20 publications
1
19
0
4
Order By: Relevance
“…Similar systematic reviews evaluating the effect of VAS in postpartum women came to similar conclusions. Supplementation with VA increased serum and breastmilk VA; however, the effect was limited to the short term and when maternal baseline concentrations were low ( 72 ). Another systematic review evaluated high-dose VA on blood and milk VA and found significant elevation in milk VA in 9 of 11 studies and significant elevation in blood in 4 of 9 studies compared with control groups ( 73 ).…”
Section: Resultsmentioning
confidence: 99%
“…Similar systematic reviews evaluating the effect of VAS in postpartum women came to similar conclusions. Supplementation with VA increased serum and breastmilk VA; however, the effect was limited to the short term and when maternal baseline concentrations were low ( 72 ). Another systematic review evaluated high-dose VA on blood and milk VA and found significant elevation in milk VA in 9 of 11 studies and significant elevation in blood in 4 of 9 studies compared with control groups ( 73 ).…”
Section: Resultsmentioning
confidence: 99%
“…Penelitian Matamoros menunjukkan 50% dari 79 sampel ibu, kandungan vitamin A dalam ASI tidak memenuhi rekomendasi kebutuhan untuk bayi (5) . Prevalensi defisiensi vitamin A lebih tinggi (6,9%) pada kelompok berpenghasilan rendah dibanding pada kelompok berpenghasilan tinggi (3,7%) (6) Suplementasi Vitamin A dalam masa nifas meningkatkan konsentrasi serum retinol dan ASI, namun ini hanya relevan ketika konsentrasi serum retinol ibu sebelumnya rendah (7) Kurangnya efek pada kematian ibu dan bayi serta terhadap morbiditas, suplementasi vitamin A pascapersalinan ibu menawarkan manfaat yang masih terbatas (1,8) . Penelitian Tomiya et all menunjukkan tidak ada perbedaan yang signifikan antara konsentrasi retinol dalam ASI antara kelompok 400.000 IU vs 200.000 IU (9) .…”
Section: Pendahuluanunclassified
“…Furthermore, in humans, an insufficient supply of vitamin A to the fetus is associated with organ malformations, preterm birth, and low neonatal stores, which increase the risk of infectious diseases and could exert a negative effect on health later in life [36,[45][46][47]. Pregnant and breastfeeding women are considered to be at risk due to their higher demand for micronutrients, and should be advised to consume enriched products with β-carotene or, even better, vitamin A plus β-carotene, in order to avoid nutritional deficits [16,19,25,[31][32][33][34]48].…”
Section: Vitamin a Dietary Sources Availability And Requirementsmentioning
confidence: 99%
“…Due to the positive relationship between dietary intake of carotenoids and breastmilk concentration, breastfeeding mothers should have a diet abundant in this micronutrient. Therefore, the recommended dietary allowance (RDA) is higher for pregnant and lactating women than for non-pregnant women [17,19,31,[41][42][43]48,75,90,92].…”
Section: Vitamin a Concentration In Milkmentioning
confidence: 99%
See 1 more Smart Citation